Influence of different concentrations of nitric oxide on fruit quality of sweet pepper and mango under mixed loading conditions - Samar A.M.A. SHAARAWI; Mohamed A.A. ABDULLAH; Huda A. IBRAHIM; Hayam A.A. MAHDY (Notulae Scientia Biologicae, 2023)
In this study, mango fruits (Mangifera indica L.) were stored together with sweet peppers to simulate mixed load shipping conditions. Sheets of Nitric oxide with different concentrations (40, 60 and 80 ml/l) were placed in mango packages. Sets with different treatments of treated and or untreated (control) mango fruits were placed together with sweet peppers, then each of treatments was kept separated in cold-storage rooms at 10 °C + 90% RH, for 35 days. Samples from mangos and sweet peppers were examined at 7 days’ intervals for physical and chemical quality parameters.  For both mango fruits and sweet peppers nitric oxide at 60 ml/l treatment showed a significant reduction of weight loss and decay percentages, and maintained general appearance, fruit firmness, total soluble solids (TSS), ascorbic acid content, and total sugars. Total chlorophyll also was steadily maintained. Hence nitric oxide at 60 ml/l significantly proved to be a potential treatment to delay ripening and keeping better overall quality attributes of both mango and sweet peppers fruits stored together as compared to other treatments and control under cold storage conditions.